2012
DOI: 10.1093/nar/gks858
|View full text |Cite
|
Sign up to set email alerts
|

p53-Independent regulation of p21Waf1/Cip1 expression and senescence by PRMT6

Abstract: p21 is a potent cyclin-dependent kinase inhibitor that plays a role in promoting G1 cell cycle arrest and cellular senescence. Consistent with this role, p21 is a downstream target of several tumour suppressors and oncogenes, and it is downregulated in the majority of tumours, including breast cancer. Here, we report that protein arginine methyltransferase 6 (PRMT6), a type I PRMT known to act as a transcriptional cofactor, directly represses the p21 promoter. PRMT6 knock-down (KD) results in a p21 derepressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
75
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 37 publications
13
75
0
2
Order By: Relevance
“…These functions agree with the nuclear localization of Prmt6 (25). To date, many target genes of Prmt6 have been reported, including HoxA2 (17), thrombospondin-1 (26), p21 (20), p27 (27), p53 (21), Oct4 and Nanog (28), CD41 (29), and IL-6 (24).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…These functions agree with the nuclear localization of Prmt6 (25). To date, many target genes of Prmt6 have been reported, including HoxA2 (17), thrombospondin-1 (26), p21 (20), p27 (27), p53 (21), Oct4 and Nanog (28), CD41 (29), and IL-6 (24).…”
supporting
confidence: 82%
“…Other reports demonstrate that PRMT6 is up-regulated in diverse cancer types, promoting growth and suppressing apoptosis, which is of potential significance for cancer therapeutics (19,20,26). These studies suggest that the balance of Prmt6 plays an important role in proliferation and apoptosis and that further study of this protein may prove of importance to developmental biology and anticancer research.…”
Section: Discussionmentioning
confidence: 68%
“…The critical role for p21 in senescence regulation, even independently of p53, was supported by two recent articles describing p21-dependent programmed senescence during mouse development (2, 3). As a further support to the central role for p21 in senescence, recent studies have demonstrated p21-induced senescence in p53-defective cancer cell lines (17,(19)(20)(21) and tumors in vivo (22,23 Regulation and therapeutic targeting of E2F1-driven cancer cell senescence resistance. Activity and expression of transcription factor E2F1 is regulated by upstream tumor suppressors p53, p16, and RB and by positive feedback loop between E2F1 and its target gene CIP2A.…”
Section: P21 Mediates P53-induced Senescencementioning
confidence: 89%
“…According to several studies, upregulation of p21 transcription can be through p53‐dependent pathways or p53‐independent pathways 49, 50, 51, 52. The promoter of p21 contains two conserved p53‐binding sites required for p53 responsiveness after DNA damage 53.…”
Section: Discussionmentioning
confidence: 99%